Metabolome and transcriptome analyses reveal molecular responses of two potato (Solanum tuberosum L.) cultivars to cold stress - Li, Xiang; Zheng, Zhenzhen; Zhou, Yun; Yang, Shenglong; Su, Wang; Guo, Heng; Ye, Guangji; Wang, Jian (Frontiers in Plant Science, 2025)
IntroductionPotato (Solanum tuberosum L.), as an important food crop on the Qinghai-Tibet Plateau, is prone to low temperature and frost damage during the seedling stage, causing economic losses for farmers.MethodsIn this study, metabolome and transcriptome analyses were conducted on the leaves of Atlantic (cold-resistant) and KY140 (cold-sensitive) potato varieties following exposure to cold stress (CS). ResultsAfter CS, 298 and 195 differentially accumulated metabolites (DAMs) were identified in Atlantic and KY140, respectively, with 124 common DAMs, including lipids, flavonoids, alkaloids, organic acids, amino acids and their derivatives, nucleotides and their derivatives, lignans and coumarins, phenolic acids, and terpenoids. A total of 6928 and 2428 differentially expressed genes(DEGs) were identified in Atlantic and KY140, respectively, with 1131 common DEGs. Joint analysis of DAMs and DEGs, “flavonoid-related metabolism,” “lipid metabolism,” and “amino acid metabolism” were plotted. Cinnamic acid, caffeic acid, naringenin, and γ-aminobutyric acid (GABA) might participate in the regulation of potato resistance to CS. The genes StPAL(Soltu.Atl.09_2G005110) and StGAD(Soltu.Atl.11_3G000340) encode enzymes responsible for the biosynthesis of cinnamic acid and GABA, respectively, suggesting their involvement in the regulation of cold resistance in potato. DiscussionOur results provided novel insights into the molecular mechanisms underlying cold resistance in potato.